Estimation of Dynamic Discrete Choice Models by Maximum Likelihood and the Simulated Method of Moments - Philipp Eisenhauer; James J. Heckman; Stefano Mosso (Institute for the Study of Labor (IZA), 2014)
We compare the performance of maximum likelihood (ML) and simulated method of moments (SMM) estimation for dynamic discrete choice models. We construct and estimate a simplified dynamic structural model of education that captures some basic features of educational choices in the United States in the 1980s and early 1990s. We use estimates from our model to simulate a synthetic dataset and assess the ability of ML and SMM to recover the model parameters on this sample. We investigate the performance of alternative tuning parameters for SMM.
Keywords: C13; C15; C35; I21; 330; returns to education; dynamic discrete choice; simulation-based estimation